Legal and administrative requirements in Shari’ah compliant hospitality services - Ramli, Noriah; Zawawi, Majdah; Abas, Afridah; Azmi, Ida Madieha (2019)
The Muslim Friendly Hospitality industry (MFH) includes services such as tourism accommodations primarily hotels, food services, tourism packages and tour guides services. These areas are fast developing tourism products and services in the MFH industry. According to the Global Muslim Travel Index (GMTI) 2018, Malaysia tops the chart as the best Muslim travel destination in the world (Brown, 2017 and Global Muslim Travel Index, 2018). Malaysia has retained this position since 2011 (Crescentrating, 2011). Hence, in order to ensure a healthy MFH ecosystem, it is necessary to ensure that the existing and future infrastructure, both legally and administratively, are in place to ensure Malaysia remains as the top global Muslim friendly destination. Tourism infrastructure clearly needs domestic development before international inbound tourism can occur. It is timely that Malaysia takes concrete steps to develop a legal and administrative framework to promote MFH as the preferred choice for travellers within the country and globally. The impetus for this project/research is borne out of the need to propel Malaysia forward in the tourism industry. One of the ways to make this possible is through the creation of the relevant legal and adminsitrative framework. This report is divided into FOUR main parts: (i) The first part of this report provides crucial information to the understanding of critical concepts relating to halal tourism.. The current practice, features, and legal and administrative requirements for Muslim Friendly Hospitality and Services will help to boost Malaysia’s potential to become one of the prominent destinations for Muslim tourists. (ii) This leads to part two which highlights the existing as well as the proposed legal and administrative framework. This is done by discussing the Malaysian Standard on Muslim Hospitality and Services Requirements (MS2610:2015). This part also includes an explanation on the development of the Manual Procedure for Muslim Friendly Hospitality Services Certification procedures as well the Muslim Friendly Hospitality Audit Check list. To further strengthen the implementation of Muslim Friendly Hospitality Services, this research has also developed several sets of training modules and guide books for Muslim Friendly Tourism Accommodation, Muslim Friendly Tour Guides, and Muslim Friendly Tourism Packages. (iii) Part three elaborates on the research methodology utilised in achieving the aims and objectives of this research. This includes round table discussions/focus group discussions, field work/field research, structured interviews, case studies and market surveys. (iv) Finally, part four of this report provides the the findings of the research and proposes several suggestions on the way forward for the Malaysian Muslim friendly hospitality industry.